Security in NFC-based application : analysis of its threats and countermeasure - Tabet, Nour Elhouda (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2013)
Near Field Communication (NFC) is a recent technology that has been rapidly implemented in different areas in the market. NFC is a wireless communication technology that enables fast and low cost transaction to be conducted. This technology is based on RFID technology which has been in the market for over a decade. However, NFC comes to serve the areas where RFID failed to do so; areas that requires short range and a quick transaction. NFC has been already implemented in various fields including payment systems, access control systems, monitoring systems, ticketing systems, and many more. However, NFC technology is very recent in comparison to the other wireless technologies. This fact highlights the importance of carrying further studies that investigates the readiness of NFC technology as a service enabler, specifically in low risk tolerance systems such as payment systems. Google wallet is one of the first movers toward implementing NFC into a payment system called Google wallet. Yet, attackers could not resist the temptation of breaking such a new technology. Relay attack was introduced as one of the main threats that have been exploited by attackers. This research studies the security threats and gaps in NFCbased systems, and examines the feasibility of several countermeasures such as setting a time constraint, applying Distance-bounding protocol, and the possibility of procedural improvement.